Analisis Pengaruh Corporate Social Responsibility dan Ukuran Perusahaan terhadap Keputusan Investasi Investor Institusional pada Emiten Sektor Properti yang Terdaftar di BEI Tahun 2020–2024 - Joni Hendra; Delia Desvianti; Parida Parida; Serliana Serliana; Koni Piranda (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The shifting investment orientation that increasingly emphasizes sustainability and social responsibility demands an evaluation of non-financial factors in institutional investors' decision-making processes. This study aims to analyze the influence of Corporate Social Responsibility (CSR) and firm size on institutional investors' investment decisions among property sector issuers listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach with a causal explanatory design was employed. The sample consisted of 35 companies selected through purposive sampling based on institutional ownership, availability of annual and sustainability reports. Data were collected from secondary documentation and analyzed using multiple linear regression to test the simultaneous and partial effects among variables. The results show that CSR and firm size significantly affect investment decisions, with CSR having a stronger influence. This indicates that companies committed to social sustainability and possessing larger asset scales tend to be more trusted by institutional investors. The integration of CSR practices and company size growth serves as an effective strategy to attract investment. This study enriches the theoretical literature by reinforcing the application of signaling theory and stakeholder theory in the context of emerging capital markets, while also providing practical recommendations for companies and regulators to pay greater attention to sustainability aspects in corporate management and disclosure.